2004
DOI: 10.1016/s1607-551x(09)70166-4
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic Susceptibility Pattern of Anovaginal Isolates of Streptococcus agalactiae from Pregnant Women in Their Late Third Trimester

Abstract: Group B streptococcus (GBS) neonatal sepsis is a serious disease causing newborn mortality and long‐term neurologic sequelae. The Centers for Disease Control and Prevention (CDC) recommend third‐trimester GBS screening and intrapartum antibiotic prophylaxis for high‐risk women. The aim of our study was to identify colonized pregnant women and assess the prevalence of GBS in pregnancy and the susceptibility pattern of GBS in southern Taiwan. We performed the study at the Department of Obstetrics and Gynecology,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…The GBS strains-resistance trend toward these antibiotics is important, since erythromycin is considered first-line prophylaxis for those with allergy to penicillin. In Brazil, however, Castellano-Filho et al (2010) reported 22.7 and 50% of GBS isolates were resistant to erythromycin and clindamycin, respectively, while in Taiwan, Fu et al (2004) and Simoes et al (2007) reported that as much as 39.9% of GBS isolates were resistant to penicillin G. This highlights, the importance of ongoing population-based monitoring for trends in Talat et al 411 antimicrobial resistance (Edwards, 2006;Barcaite et al, 2008). The fact that most of our GBS isolates were resistant to gentamicin or tetracycline is in agreement with literature data (Morales et al, 1999;Al Huseini et al, 2000;Edwards, 2006;Shabayek et al, 2009) and thereby emphasizing GBS-intrinsic resistance to these antibiotics (Al Huseini et al, 2000).…”
Section: Number Of Biofilm Forming Gbs Number Of Non-biofilm Forming mentioning
confidence: 99%
See 1 more Smart Citation
“…The GBS strains-resistance trend toward these antibiotics is important, since erythromycin is considered first-line prophylaxis for those with allergy to penicillin. In Brazil, however, Castellano-Filho et al (2010) reported 22.7 and 50% of GBS isolates were resistant to erythromycin and clindamycin, respectively, while in Taiwan, Fu et al (2004) and Simoes et al (2007) reported that as much as 39.9% of GBS isolates were resistant to penicillin G. This highlights, the importance of ongoing population-based monitoring for trends in Talat et al 411 antimicrobial resistance (Edwards, 2006;Barcaite et al, 2008). The fact that most of our GBS isolates were resistant to gentamicin or tetracycline is in agreement with literature data (Morales et al, 1999;Al Huseini et al, 2000;Edwards, 2006;Shabayek et al, 2009) and thereby emphasizing GBS-intrinsic resistance to these antibiotics (Al Huseini et al, 2000).…”
Section: Number Of Biofilm Forming Gbs Number Of Non-biofilm Forming mentioning
confidence: 99%
“…Susceptibility was performed, and results interpreted according to Clinical Laboratory Standard Institute CLSI guidelines. Each strain had its susceptibility classified as sensitive, intermediate or resistant to each one of these antibiotics (Morales et al, 1999;Clinical and Laboratory Standards Institute (CLSI), 2007;Fu et al, 2004). The antibiotic tested were, 10 μg Ampicillin, 30 μg Cefepime, 30 μg ceftriaxone, 2 μg clindamycin, 15 μg erythromycin, 10 μg gentamicin, 300 μg nitrofurantoin, 30 μg Tetracycline and 30 μg vancomycin.…”
Section: The Susceptibility Testesmentioning
confidence: 99%